ANALISIS PERBANDINGAN TINGKAT LITERASI ZAKAT PETANI BERDASARKAN PRODUKTIVITAS PERTANIAN MELALUI PENGUKURAN INDEKS LITERASI ZAKAT (ILZ) - Sabrina Divaning Tyas; Akhris Fuadatis Sholikha (JURNAL ILMIAH NUSANTARA, 2025)
Low zakat literacy remains a challenge in optimizing zakat collection in Indonesia, especially in rural areas where most of the population works as farmers. Zakat literacy plays an important role in increasing awareness and compliance in fulfilling zakat obligations, particularly agricultural zakat. This study aims to analyze and compare the zakat literacy levels of farmers based on agricultural productivity using the Zakat Literacy Index (ILZ) in Pandansari and Cipetung Villages, Paguyangan District, Brebes Regency. This research uses a quantitative approach with a comparative method. Data were collected through a questionnaire based on ILZ indicators from Puskas BAZNAS. According to Slovin’s formula, the ideal number of respondents was 269, but only 228 valid responses were obtained due to time constraints, geographical challenges, and varying participation. Data analysis included descriptive statistics, normality test, homogeneity test, and the non-parametric Mann-Whitney U test. The results show that the zakat literacy level of farmers in Pandansari is in the moderate category (score 62.2), while Cipetung is in the low category (score 58.01). The Mann-Whitney U test produced a significance value of < 0.001, indicating a significant difference in zakat literacy levels between the two villages. Therefore, the alternative hypothesis for the third research question is accepted.